2008
DOI: 10.1038/jcbfm.2008.127
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Sedentarism Decrease Vascularization and VEGF Levels in the Rat Substantia Nigra. Implications for Parkinson's Disease

Abstract: It is not known if aging induces changes in nigral vascularization and nigral vascular endothelial growth factor (VEGF) levels similar to those previously reported for Parkinson's disease (PD). In this study nonexercised rats displayed age-dependent decreases in the density of nigral microvessels and VEGF mRNA expression, which were reversed by physical exercise. Such changes may enhance the vulnerability of dopaminergic neurons and the risk of developing PD, and may be reduced by exercise. Furthermore, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 15 publications
(40 reference statements)
1
38
0
Order By: Relevance
“…However, Ndubuizu et al (2009) also reported no significant change in basal VEGF message with age in rat brain cortex, and squamous cell carcinoma tumors from young vs. aged mice displayed similar VEGF mRNA levels (Bojovic and Crowe, 2010). VEGF expression might be altered with aging in discrete brain regions not examined here – e.g., the substantia nigra pars compacta (Villar-Cheda, et al, 2009) – and/or detected age-related changes in VEGF gene activity may correspond more so to other neural cell roles (e.g., neuroprotective/neurogenic) rather than angiogenesis. It is tempting to speculate that, in the absence of concurrent elevation of VEGF, the noted age-related increase in hippocampal expression of Ang2 (the natural antagonist for Ang1) might facilitate vessel destabilization and regression, and muted cerebral angiogenesis during normal aging.…”
Section: 0 Discussionmentioning
confidence: 99%
“…However, Ndubuizu et al (2009) also reported no significant change in basal VEGF message with age in rat brain cortex, and squamous cell carcinoma tumors from young vs. aged mice displayed similar VEGF mRNA levels (Bojovic and Crowe, 2010). VEGF expression might be altered with aging in discrete brain regions not examined here – e.g., the substantia nigra pars compacta (Villar-Cheda, et al, 2009) – and/or detected age-related changes in VEGF gene activity may correspond more so to other neural cell roles (e.g., neuroprotective/neurogenic) rather than angiogenesis. It is tempting to speculate that, in the absence of concurrent elevation of VEGF, the noted age-related increase in hippocampal expression of Ang2 (the natural antagonist for Ang1) might facilitate vessel destabilization and regression, and muted cerebral angiogenesis during normal aging.…”
Section: 0 Discussionmentioning
confidence: 99%
“…This suggests that overactivity of the Ang II/AT1/Nox axis plays a key role in aging-related iron and ferritin increase in the substantia nigra (Garrido-Gil et al, 2013a). The aging-associated upregulation of Ang II/AT1/Nox activity may lead to upregulation of iron storage by microglia and induce a pro-oxidative pro-inflammatory state and higher vulnerability of dopaminergic cells to degeneration with aging (Collier et al, 2007; Villar-Cheda et al, 2009, 2012b). …”
Section: Interactions Between Ras and Other Microglial Polarization Rmentioning
confidence: 99%
“…In addition, exercise has been shown to increase both angiogenesis and neurogenesis in regions of the brain. The hippocampal neurogenic response to exercise is thought to be mediated by VEGF expressed within peripheral organs (Fabel et al 2003; Villar-Cheda et al 2009). Thus, which organs increase VEGF expression in response to an acute exercise bout and the gene regulatory mechanisms that control VEGF expression in each organ remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%